Efektivitas Konseling Motivational Interviewing (MI) dalam Mengurangi Agresivitas pada Siswa yang Kecanduan Game Online - Pranata, Dian; Kumara, Agus Ria; Bhakti, Caraka Putra; Saputra, Wahyu Nanda Eka (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Aggressiveness among adolescents has become an increasingly complex psychosocial issue in line with the rising prevalence of online gaming addiction in the digital era. This study aimed to examine the effectiveness of Motivational Interviewing (MI) and Aggression Replacement Training (ART) in reducing aggressiveness among senior high school students with tendencies toward online gaming addiction. A quantitative approach with a quasi-experimental design was employed, using a mixed repeated-measures ANCOVA with online gaming addiction as a covariate. The participants consisted of 12 eleventh-grade students who exhibited high levels of aggressiveness and online gaming addiction at baseline. The results indicated that both interventions significantly reduced students’ aggressiveness from the pre-intervention phase to the post-intervention and follow-up stages. However, Motivational Interviewing demonstrated greater effectiveness than Aggression Replacement Training, as evidenced by larger, more consistent, and more sustained reductions in aggressiveness across all measurement points. In addition, a significant relationship was found between aggressiveness and online gaming addiction, underscoring the importance of controlling digital behavioral addiction when implementing psychological interventions targeting aggressive behavior. Based on these findings, the study concludes that Motivational Interviewing represents a more effective and contextually appropriate counseling approach for reducing aggressiveness associated with online gaming addiction among adolescents. This study contributes to the development of evidence-based guidance and counseling practices in school settings, particularly in addressing contemporary psychosocial challenges faced by adolescents in the digital era